L2 learners' ability to recognize ironic online comments and the effect of instruction. (April 2022) - Prichard, Caleb; Rucynski, John
Abstract: Verbal irony is common in Web 2.0 communication but detecting it can be challenging. Language learners may have even more difficulty with verbal irony, including meaning reversal irony (e.g., sarcasm, jocularity) and meaning replacement irony (surrealistic irony), possibly leading to miscommunication and demotivation. The study involves two experiments. The first investigates the ability of Japanese learners of English ( N = 148) to detect verbal irony in social media comments using a validated instrument. The second experiment examines the effect of instruction on recognizing verbal irony using a pre-posttest, control group design. The first experiment found that the participants had some difficulty with meaning reversal irony (e.g., sarcasm), especially when cued by incongruous comments by the same person. The second experiment suggested that instruction on detecting verbal irony led to gains in the experimental group's ability to recognize irony when marked by paralinguistic cues. Implications for educators are discussed.